2007
DOI: 10.3892/ijo.30.6.1413
|View full text |Cite
|
Sign up to set email alerts
|

Potentiated antitumor effects of the combination treatment with statins and pamidronate in vitro and in vivo

Abstract: The aim of the present study was to examine the potential antitumor activity of lovastatin and other statins together with pamidronate, a second generation bisphosphonate (BP), against tumor cell lines. Cytostatic/cytotoxic effects were measured using crystal violet assay. Regulation of the cell cycle and induction of apoptosis were evaluated using flow cytometry and Western blotting, migration of tumor cells was measured in a scratch wound assay and their invasiveness was measured with a Matrigel-invasion ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…Statins were previously reported to enhance the effect of anticancer drugs and radiation therapy in other cancer cells, such as prostatic and pancreatic cancer cells (38)(39)(40), and the results of this study demonstrated that statins combined with anticancer drugs such as gemcitabine, cisplatin and 5-FU enhanced their effects in cholangiocarcinoma cells (Fig. 5).…”
Section: Discussionmentioning
confidence: 52%
“…Statins were previously reported to enhance the effect of anticancer drugs and radiation therapy in other cancer cells, such as prostatic and pancreatic cancer cells (38)(39)(40), and the results of this study demonstrated that statins combined with anticancer drugs such as gemcitabine, cisplatin and 5-FU enhanced their effects in cholangiocarcinoma cells (Fig. 5).…”
Section: Discussionmentioning
confidence: 52%
“…The importance of isoprenoid synthesis and prenylation in pancreatic cancer growth was reinforced when lovastatin in combination with pamidronate, an inhibitor of FPP synthase, was demonstrated to inhibit farnesylation and geranylgeranylation, and to exhibit synergistic antitumor effects in vitro and in vivo (55). Furthermore, statins were shown to improve survival and reduce tumor burden in animal models of pancreatic cancer compared with controls at doses below the maximum recommended dose for humans (56).…”
Section: Mechanisms Of Action and Evidence Of Antitumor Effects Of Stmentioning
confidence: 99%
“…Thus, fluvastatin was shown to enhance the antiproliferatory effect of gemcitabine in MIA PaCa-2 pancreatic cancer cells [5]. Besides their in vitro effects, statins have been shown to inhibit pancreatic tumor growth in vivo [3,5,7]. In a recent study performed on nude mice it was shown that different statins decreased the tumor growth of transplanted Capan-2 cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that statins inhibit growth of pancreatic cancer cell lines in vitro and sensitize them for cytostatic drugs [3][4][5][6]. Gemcitabine, which is presently used for the treatment of pancreatic cancer, is one of these drugs.…”
Section: Introductionmentioning
confidence: 99%